Inflammatory endobronchial polyps unleashing recurrent pneumothorax: a case report - Daut, Ummi Nadira; Faisal Thena, Muhammad Halmii; Hui‐Xin, Tan; Nasaruddin, Mona Zaria; Abdul Rahaman, Jamalul Azizi (Wiley Open Access, 2024)
Inflammatory endobronchial polyps (IEPs) are rare benign lesions that originate from the bronchial mucosa. While pneumothorax is a well‐known complication of various pulmonary conditions, its association with IEPs is exceedingly uncommon and poorly understood. This case report presents a unique and explosive encounter of a patient with an inflammatory endobronchial polyp who experienced a pneumothorax, shedding light on the clinical presentation, diagnostic challenges, and management strategies for this rare entity.